2004
DOI: 10.1248/jhs.50.654
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Proteoglycan Release from Cultured Vascular Endothelial Cell Layers by Sodium Spirulan

Abstract: Our previous study suggested that sodium spirulan (Na-SP) stimulated the release of proteoglycans from cultured vascular endothelial cell layers. In the present study, we characterized the stimulatory effect of Na-SP on endothelial proteoglycan release from the viewpoint of the Na-SP structure. The following results were obtained: Na-SP is a potent stimulator of endothelial proteoglycan release. The stimulatory effect of Na-SP disappears with desulfation or removal of sodium ion. Depolymerized Na-SPs (M r ~147… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…18) Although not only Na-SP but also other particular polysaccharides such as heparin, dextran sulfate and hyaluronan can stimulate endothelial PG release, 19) it has been unclear whether these polysaccharides act on the release of both HSPGs and CS/DS PGs, as does Na-SP. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18) Although not only Na-SP but also other particular polysaccharides such as heparin, dextran sulfate and hyaluronan can stimulate endothelial PG release, 19) it has been unclear whether these polysaccharides act on the release of both HSPGs and CS/DS PGs, as does Na-SP. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18) Not only Na-SP, but also heparin, dextran sulfate and hyaluronan, stimulates the release of PGs from vascular endothelial cell layers. 19) However, it was shown that the stimulation by heparin, dextran sulfate and hyaluronan occurred mainly in the HSPG release, whereas that by Na-SP did in both HSPGs and CS/DS PGs. In other words, Na-SP is a particular polysaccharide that strongly stimulates the release of CS/DS PG, specifically biglycan, from vascular endothelial cell layers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…11) In vascular endothelial cells, Na-SP elevates the fibrinolytic activity of vascular endothelial cells through inhibition of the secretion of plasminogen activator inhibitor type 1. 12) In addition, Na-SP promotes the secretion of anticoagulant proteoglycans 13) such as perlecan and biglycan, 14) as well as exhibiting an antithrombin activity through activation of heparin cofactor II. 15,16) We hypothesized that CA or SCA may inhibits the proliferation of vascular smooth muscle cell proliferation, as does natural or semi-synthetic polysaccharides, including Na-SP, heparin, 17) pentosan polysulfate 18) and fucoidan.…”
mentioning
confidence: 99%